2012
DOI: 10.1364/oe.20.028039
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmon microscopic sensing with beam profile modulation

Abstract: Surface Plasmon microscopy enables measurement of local refractive index on a far finer scale than prism based systems. An interferometric or confocal system gives the so-called V(z) curve when the sample is scanned axially, which gives a measure of the surface plasmon propagation velocity. We show how a phase spatial light modulator (i) performs the necessary pupil function apodization (ii) imposes an angular varying phase shift that effectively changes sample defocus without any mechanical movement and (iii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…In the work reported here and previously, 8,9 the interference occurs between different parts of the illumination beam, so that one portion of the illumination beam acts as a reference. This approach facilitates our aim to obtain fine phase measurements between different paths within the same beam.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…In the work reported here and previously, 8,9 the interference occurs between different parts of the illumination beam, so that one portion of the illumination beam acts as a reference. This approach facilitates our aim to obtain fine phase measurements between different paths within the same beam.…”
Section: Introductionmentioning
confidence: 69%
“…This confocal arrangement therefore ensures that the path of the SPs is well defined by the optical configuration rather than their propagation length. We have shown in subsequent publications 8,9 how a spatial light modulator conjugate with the back focal plane is effective in allowing for different processing methods that overcome mechanical scanning or allow the amplitude and phase of the SP to be extracted directly, thus providing an exceptionally robust means of processing the signal. For instance, the spatial light modulator (SLM) can be used to change the phase of P1 relative to P2 so that phase stepping may be performed which allows the phase associated with SP to be extracted directly.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…
We have developed surface plasmon interferometric microscope and demonstrated that by integrating a phase spatial light modulator (SLM) on conjugate back focal plane of confocal microscope objective lens, this enables us to perform surface plasmon phase imaging and phase sensing using phase stepping interferometry over well confined region [1][2][3][4][5][6]. In this paper, we address one of the key limitations of the system, which is data acquisition time.
…”
mentioning
confidence: 99%